Kesan bencana terhadap kesihatan dan keselamatan sukarelawan - Nur Hafizah Md Akhir; Azlinda Azman; Noremy Md Akhir (Penerbit Universiti Kebangsaan Malaysia, 2020)
Disaster often occurs unexpectedly and the impact is in loss of property, life and human well-being. During the disaster, vary humanitarian agencies respond in helping government on the recovery process. Volunteers are one of the most major roles in the disaster relief work. However, the risks of disasterous situation have made it difficult for volunteers. The challenges of disaster also affected toward volunteer’s health and safety. Exploring the impact of a disaster can be on volunteers’ health and safety. Therefore, a study of the impact on volunteers involved in floods disaster relief has been carried out. Qualitative methods using case study have been used. The researchers also use purposive sampling techniques for selecting 27 respondents. In-depth interviews were conducted with 27 respondents who met the prescribed sampling criteria. The results show that health, safety, stress and psychological disorder are the effects of disaster on volunteers. Discussions were focused on the effects of disaster toward volunteers’ health and safety